208k views
4 votes
Please solve this :)​

Please solve this :)​-example-1
User Klooven
by
5.2k points

2 Answers

3 votes

Answer:

49

Explanation:


36 - {5}^(2) + {7}^(2) - 11

[P.E.D.M.A.S rule] (First exponents)

= 36 - 25 + 49 - 11. (Then addition)

= 36 + 49 - 25 - 11

= 85 - 36. (At last subtraction)

= 49 (Ans)

User David Thery
by
6.3k points
1 vote

Answer:

=25+2squared

Explanation:

simple like terms

36-11=25

-5squared+7squared=2squared

=25+2squared

User Morgan Green
by
5.7k points